Overexpression of Grainyhead-like 3 causes spina bifida and interacts genetically with mutant alleles of Grhl2 and Vangl2 in mice. (4th September 2018) - De Castro, Sandra C P; Gustavsson, Peter; Marshall, Abigail R; Gordon, William M; Galea, Gabriel; Nikolopoulou, Evanthia; Savery, Dawn; Rolo, Ana; Stanier, Philip; Andersen, Bogi; Copp, Andrew J; Greene, Nicholas D E
Abstract: The genetic basis of human neural tube defects (NTDs), such as anencephaly and spina bifida (SB), is complex and heterogeneous. Grainyhead-like genes represent candidates for involvement in NTDs based on the presence of SB and exencephaly in mice carrying loss-of-function alleles of Grhl2 or Grhl3 . We found that reinstatement of Grhl3 expression, by bacterial artificial chromosome (BAC)-mediated transgenesis, prevents SB in Grhl3 -null embryos, as in the Grhl3 hypomorphic curly tail strain. Notably, however, further increase in expression of Grhl3 causes highly penetrant SB. Grhl3 overexpression recapitulates the spinal NTD phenotype of loss-of-function embryos, although the underlying mechanism differs. However, it does not phenocopy other defects of Grhl3 -null embryos such as abnormal axial curvature, cranial NTDs (exencephaly) or skin barrier defects, the latter being rescued by the Grhl3-transgene. Grhl2 and Grhl3 can form homodimers and heterodimers, suggesting a possible model in which defects arising from overexpression of Grhl3 result from sequestration of Grhl2 in heterodimers, mimicking Grhl2 loss of function. This hypothesis predicts that increased abundance of Grhl2 would have an ameliorating effect in Grhl3 overexpressing embryo. Instead, we observed a striking additive genetic interaction between Grhl2 and Grhl3 gain-of-function alleles. Severe SB arose in embryos in which both genes were expressed at moderately elevated levels that individually do not cause NTDs. Furthermore, moderate Grhl3 overexpression also interacted with the Vangl2 Lp allele to cause SB, demonstrating genetic interaction with the planar cell polarity signalling pathway that is implicated in mouse and human NTDs.